The Impact Of Gedi Leaf Extract On Rice Flour Layer Cake Quality - Chadijah Mardhia Fadhilla; Anni Faridah (Universitas Negeri Padang, 2021)
This study will look at the impact of utilizing gedi leaf extract in amounts of 0 ml, 8 ml, 14 ml, and 20 ml on the quality of rice flour layer cakes in organoleptic tests such as shape, color, scent, texture, and taste. This is a quantitative study that uses a completely randomized design approach (CRD) with three repetitions and employs a true experimental method. In August 2021, this study was carried out in the Workshop IKK Culinary Art, FPP, UNP. Primary data was collected from 5 limited panelists who are lecturers in UNP Culinary Art’s Family Welfare Science focus by completing out the organoleptic test format for the sample. If Fcount > Ftable, the data were examined using Analysis of Variance (ANOVA), and if Fcount > Ftable, Duncan's test was used. The results revealed that gedi leaf extract had an impact on color (moss green), aroma (gedi leaf smell), and taste. The rectangular shape measuring 6 cm x 4.5 cm x 1.5 cm gets the highest overall achievement score of 3.33 (0 ml and 8 ml), the uniformity of the layers gets 3.67 (20 ml), the color is moss green gets 3.27 (20 ml), white gets 2.67 (20 ml), the fragrant aroma of gedi leaves gets 3.00 (20 ml), the fragrant aroma of coconut milk gets 3.13 (0 ml), and the chewy texture gets 3.60. (8 ml, 14 ml and 20 ml), 3.27 (0 ml) was the soft texture, 3.33 (0 ml) was the sweetness of sugar, and 3.07 was the savory taste of coconut milk (0 ml). The usage of gedi leaf extract in various doses resulted in the effects of color quality (moss green), aroma (fragrance of gedi leaves), and taste. The color will be more concentrated the more gedi leaf extract is applied.